Elevation‐dependent response of snow phenology to climate change from a remote sensing perspective: A case survey in the central Tianshan mountains from 2000 to 2019. (20th August 2021) - Wang, Huadong; Zhang, Xueliang; Xiao, Pengfeng; Zhang, Ka; Wu, Senyao
Abstract: Alpine snow is an important water resource in arid/semi‐arid regions and sensitive to climate change. However, the response of snow phenology to climate change in different elevations remains unclear in mountain areas because of limited observation stations. In this study, the vertical difference of snow phenology and its response to climate change in high mountains are explored by using multi‐source remote sensing data from 2000 to 2019, taking the north slope of Central Tianshan Mountains as the study area. The results show that: (1) The temporal changes of snow cover days (SCD), snow cover onset date (SCOD), and snow cover end date (SCED) in different altitudes are various and contribute to the general change trends of the extended SCD, the advanced SCOD, and the advanced SCED from the hydrological year 2000 to 2018; (2) The snow phenology is significantly related to the changed temperature and/or precipitation in most altitudes, except for the SCD and SCOD in high altitudes, where the large temporal changes of temperature and precipitation lead to the complicated correlations in these altitudes; (3) The altitude threshold of 3600 m is identified to separate the relative importance of temperature and precipitation for SCD and SCOD, where the temperature shows a higher importance than precipitation below the altitude threshold, and neither temperature nor precipitation shows constant higher importance above the altitude threshold. As for SCED, the temperature is consistently more important than precipitation in most altitudes. Abstract : Correlation coefficients between the snow phenology of SCD (a), SCOD (b), SCED (c) and temperature/precipitation in each altitude belt, where the dashed line indicates the correlation coefficient at the 95% significance level.